Instant Prezi starter : a user-friendly, step-by-step introductory guide to using Prezi, a web-based presentation application program ideal for engaging your audience /: a user-friendly, step-by-step introductory guide to using Prezi, a web-based presentation application program ideal for engaging your audience. (2013) - Unknown
No abstract available